Social organization as a correctional ideology: Breaking new ground - Astone, Nicholas A. (American journal of criminal justice, 1987)
This paper examines the importance of the prison environment and its social organization as factors which reinforce the continued socialization of criminal careers. The authors analyze contemporary research findings within the context of prison administration and conclude that if behavioral change is to become a realistic by-product of incarceration, then we may need to reformulate the correctional ideology upon which penal policies rest. A social organization framework; consistant with empirical data, is then provided as the basis for an ideology leading to new generation prisons.